Communicating Branch of the Mental Nerve and Facial Nerve - Hirouchi, Hidetomo; Suzuki, Ryu; Morimoto, Ichiro; Oyanagi, Teruaki; Chen, Hsiu-Kuo; Takahashi, Akihiro; Yamamoto, Masahito; Abe, Shinichi (International Journal of Human Anatomy, 2021)
As peripheral branches of the mandibular nerve, the mental nerve and facial nerve communicate with each other. However, investigations have not always been described in the classic anatomical texts. It remains unknown how nerve fibers of this communicating branch converge at the micro level. Thus, the objective of the present study was to observe in detail the macro and micro levels of the communicating branch of mental and facial nerves. We used five cadavers (10 samples) to conduct experiments in anatomical practice at Tokyo Dental College. A macroscopic observation was made, and the communicating branch of the mental and facial nerves was removed as a single mass. We created serial sections of this branch using the standard method and observed communicating branches of these two nerves under microscopy. As a result, the communicating branch of the mental and facial nerves was completely fused at the perineurium level. It has been reported that the mental nerve includes a small amount of autonomic nerve fiber. As for these findings, similar findings were observed for all 5 bodies and 10 sides. Thus, we believe that autonomic nerve fibers derived from the facial nerve converge with the mental nerve via this communicating branch.
Keywords: mental nerve; facial nerve; marginal mandibular branch; communicating branch; macro anatomy; micro anatomy